Understanding co-creativity in real-world problem solving in project-based learning in higher education - Isaac, Guillaume; Romero, Margarida; Barma, Sylvie (Revue internationale du CRIRES / CRI_SAS international Journal)

(untitled) (Centre de recherche et d’intervention sur la réussite scolaire, 2022)
The present study constitutes a preliminary effort to frame co-creativity, project-based learning and real-world problem-solving under a cultural historical activity theory framework. The paper establishes co-creativity as collective concept formation in the wild and collective mediation as primary elements for the study of real-world problem solving in higher education. This study aims at bridging gaps between co-creative real-world problem solving in higher education and knowledge, competency, action between higher education and the real world.